AB0321 Unfavourable body composition is associated with inflammation in patients with rheumatoid arthritis. (23rd January 2014) - Konijn, N.; van Tuyl, L.; Bultink, I.; Lems, W.; van Bokhorst-de van der Schueren, M.
Abstract : Background: Disease activity is thought to play a pivotal role in the development of changes in body composition in patients with chronic inflammatory diseases. However, few data concerning body composition in relationship to disease activity in Rheumathoid Arthritis (RA) patients are currently available. Objectives: To examine body composition, and its relation with inflammation parameters in patients with RA. Methods: In this cross-sectional study, Body Mass Index (BMI) and Fat Free Mass Index (FFMI), using Bio-electrical Impedance Analysis, were measured in a cohort of RA patients visiting the outpatient or day treatment department of a Dutch university hospital. Inflammation parameters measured were erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP). Disease activity was assessed using the Disease Activity Score 28 (DAS28) and Rheumatoid Arthritis Disease Activity Index (RADAI); physical functioning was assessed by the Health Assessment Questionnaire Disability Index (HAQ-DI). Associations between measures of body composition and inflammation parameters were evaluated by Pearson correlation coefficients and linear regression analyses. Results: One hundred and three consecutive patients were included (79 women and 24 men), with a median age of 62 years (range 26-90 years) and a median disease duration of 8 years. On average, patients suffered from moderate disease activity (mean DAS28 score: 3.32; mean RADAI score: 3.30) and mild to moderate disability (median HAQ-DI score: 0.88). In addition, 59% of the patients showed an elevated ESR and 24% elevated CRP levels. Body composition, as investigated by BMI and FFMI showed different patterns. Whereas BMI categorized patients predominantly in the "normal" (41%) and "high" (40%) categories, FFMI showed a more divergent distribution with a relatively high number of patients in the normal (55%) and lowest (19%) categories. BMI and FFMI were both significantly positively correlated with ESR (r=0.344 and r=0.387, resp.) and CRP (r=0.386 and r=0.553, resp.) Furthermore, linear regression analyses showed that ESR (β=0.183, p=0.001) explained 18% of the variance of BMI, whereas the combined impact of elevated ESR (β=0.071, p=0.000) and male gender (β=3.247, p=0.000) in the multivariate model of FFMI was 46%. Conclusions: This cross-sectional study demonstrated a high frequency of unfavourable body composition, characterized by low muscle mass and high fat mass, in patients with RA. In addition, impaired body composition was associated with elevated parameters of inflammation, possibly reflecting the increased risk of RA patients for cardiovascular morbidity. Moreover, this study showed the limited value of BMI measurement for assessment of body composition in RA patients. Longitudinal research is needed to better determine cause and effect of both sides of the coin, i.e. undernutrition as well as overnutrition in RA patients. Disclosure of Interest: None Declared